Development of Steam-Pjbl Integrated LKPD on Molecule Shape Materials for Class X Senior High School - Pratiwi, Fefiola Isra; Effendi, Effendi (FKIP - Universitas Riau, 2023)
This study aims to produce STEAM-PjBL (Science, Technology, Engineering, Art and Mathematics-Project Based Learning) integrated LKPD on the material of Molecular Forms and determine the level of validity and practicality of the resulting LKPD. This research is a Research and Development (R&D) research using a 4-D model which consists of four steps: define, design, develop, disseminate. This research is limited to the design stage. The research instrument is a validity sheet and a practical sheet. The LKPD was validated by 6 validators consisting of 3 chemistry lecturers from FMIPA UNP and 3 chemistry teachers at SMA N 14 Padang. The LKPD was tested by 3 chemistry teachers and 30 students in class XI MIPA 5 SMA N 14 Padang. The validity data used the Aiken's v Scale and the practical data used a comparison of the students' scores with the maximum scores of students. The average Aiken's v scale is 0.89 with a very valid category. While the practicality of teachers and students obtained NP values of 0.90 and 0.87 with very practical categories.